Rigorous methodological approaches to address knowledge gaps in exercise, nutrition, immunity, and infection risk research - G. Davison; C. Chidley; A. W. Jones (Physiological Reports)
Abstract Upper respiratory tract infections (URTI) and the associated symptoms can have significant impacts for the general population and athletes (e.g., affecting training, recovery, and performance). Various factors influence the risk of URTI, including physiological stress (i.e., exercise), psychological stress, sleep, travel, nutrition, and pathogen exposure. Traditional research in exercise immunology has relied heavily on ex vivo immune markers, which lack clinical relevance and overlook immune redundancy and robustness. As such, it is unsurprising that interventions affecting these markers do not always align with URTI risk. More recently, evidence has emphasized the importance of in vivo immune markers and clinical outcomes to assess infection risk, and the role of interventions to mitigate this. Traditionally, nutritional exercise immunology research has focused only on mechanisms affecting URTI via immune modulation. However, nutritional interventions may also act via immune‐independent mechanisms (e.g., direct antipathogenic mechanisms). For future research, we recommend prioritizing clinically relevant endpoints (validated URTI logs; pathogen screening); using in vivo markers representing the integrated immune response; large sample size; and implementing stringent study controls. Experimental infection challenge models offer controlled investigations of interventions. These approaches will enhance our ability to determine the impact of exercise and nutrition on immunity and URTI outcomes in athletes.